The Efficacy of Using Countermeasures in a Model Statement Interview - Aldert Vrij; Sharon Leal; Ronald P. Fisher; Samantha Mann; Haneen Deeb; Eunkyung Jo; Claudia Castro Campos; Samer Hamzeh (European Journal of Psychology Applied to Legal Context, 2019)

(untitled)
In a countermeasures experiment, we examined to what extent liars who learn about the Model Statement tool and about the proportion of complications (complications/complications + common knowledge details + self-handicapping strategies) can successfully adjust their responses so that they sound like truth tellers. Truth tellers discussed a trip they had made; liars fabricated a story. Participants were of Lebanese, Mexican, and South-Korean origin. Prior to the interview they did or did not receive information about (i) the working of the Model statement and (ii) three types of verbal detail: complications, common knowledge details and self-handicapping strategies. We found no evidence that liars sounded like truth tellers after being informed about the Model Statement and/or types of detail we examined. Actually, veracity differences were similar across experimental conditions, with truth tellers reporting more detail and more complications and obtaining a higher proportion of complications score than liars.